A computer-aided usability testing tool for in-vehicle infotainment systems. (July 2017) - Feng, Fred; Liu, Yili; Chen, Yifan
Highlights: A software for usability testing of in-vehicle infotainment systems was developed. A digital driver model was built based on Queuing Network-Model Human Processor. The software aims to predict the usability including eyes off road time. Validations show the software could provide outputs similar to the empirical data. Abstract: This paper describes the development of a computer-aided engineering (CAE) software toolkit for designers of in-vehicle infotainment systems to predict and benchmark the system usability, such as task completion time, eye glance behaviors, and mental workload. A digital driver model was developed based on the task-independent cognitive architecture of QN-MHP (Queuing Network-Model Human Processor). At the front end of the software a graphical user interface (GUI) was developed that allows designers to create digital mockups of the designs and simulate drivers performing secondary tasks while steering a vehicle. To validate the software outputs, an experiment using human drivers was conducted on a fix-based driving simulator with a radio-tuning task as a test case. Three typical in-vehicle infotainment systems that have the function of radio tuning were investigated (a touch screen, physical buttons, and a knob). The results show that the software was able to generate task completion time, total eyes-off-road time, and mental workload estimates that were similar to the empirical data. The software toolkit has the potential to be a supplemental tool for designers to explore a larger design space and address usability issues at the early design stages with lower cost in time and manpower.